Developing a Household Flood Vulnerability Index for Managing the Risk of Flood Disasters (S/O 13584) - Hassan, Sallahuddin; Abu Bakar, Arpah; Othman, Zalila; Khalid, Mohamad Sukeri; Abu Talib, Mansor (UUM, 2018)
Due to insufficient studies notably in the East Coast region of Malaysia on the flood vulnerability analysis in a comprehensive or systematic manner, the region is foreseen to be under serious threat of floods and the awareness on flood vulnerability cannot be adequately raised among the public. Following from the 2014’s major floods, this study proposes the use of household flood vulnerability index (FVI), which follows the methodological approach of Balica and Wright (2010), to assess vulnerability levels to floods among affected households in the worst-hit districts of Kota Bharu, Kuala Krai, Kuala Terengganu, Kemaman, Kuantan and Temerloh in Kelantan, Terengganu and Pahang. With the general objective of developing a household flood vulnerability index of Malaysia (MyFVI), this study is also aimed at achieving four specific objectives namely to measure exposure, susceptibility and resilience of households, estimate the flood vulnerability levels among the households, compare the vulnerability differences among the households by the district and state and evaluate the effect of flood vulnerability on flood risk among the households. In this study, 40 vulnerability indicators in total are sourced from the primary and secondary data. Accordingly, the significant indicators have been determined through the systematic review, availability and accessibility of data. Subsequently, the indicators were categorized under the three vulnerability factors; exposure, susceptibility and resilience across the physical, social, economic and environmental vulnerabilities. While floods cannot be fully prevented despite recent developments in infrastructures, preparedness, recovery and response, enhancing community resilience is therefore needed to be a priority in flood-prone communities. The findings of this study tend to vary by the district and state, accordingly. Among others, Kuala Krai, which is found to possess the highest FVI value of 0.631 on average, is the district’s most physically, socially, and environmentally vulnerable to floods. This is followed by the districts of Kota Bharu, Kuantan, Kemaman, Temerloh and Kuala Terengganu with the associated FVI values of 0.573, 0.563, 0.554, 0.542, 0.526, respectively. Meanwhile, in the state setting, Kelantan is the most physically and socially vulnerable to floods, Pahang is the most socially and economically vulnerable to floods and Terengganu is the most environmentally vulnerable to floods. Further, by comparing across states, Terengganu is the most highly vulnerable to floods with the highest FVI value of 0.568 that is higher than the overall average. As a whole, the East Coast states of Malaysia are classified as having moderate vulnerability to floods since the states are found to have the average FVI of 0.469. \ Pertaining to the effect of flood vulnerability on flood risk, the results of regression analysis, among others, indicate that flood frequency and flood duration are key determinants under the physical vulnerability that contribute to rising flood risk of households in Kelantan. Also, evacuation routes, coping mechanisms, awareness/preparedness and warning systems constitute as key resilience indicators to reduce the flood risk formation of the households in Kelantan, Terengganu and Pahang, accordingly. Flood risk grows over time owing to the interplay of flood hazard and physical, social, economic and environmental vulnerabilities. Thus, in tackling the social aspects of vulnerability, one policy recommendation, among others, is via enhancing the social resilience to floods through improved flood warning systems among the affected communities. Also, to address key risk factors associated with the environmental conditions and natural resource management, it is recommended that the policy makers alike to promote the sustainable management of ecosystems through proper land-use strategies and development activities